Predicting the Effects of Climate Change on the Occurrence of the Toxic Dinoflagellate Alexandrium catenella Along Canada’s East Coast - Boivin-Rioux, Aude; Starr, Michel; Chassé, Joël; Scarratt, Michael; Perrie, William; Long, Zhenxia (Frontiers in Marine Science, 2021)
Alexandrium catenella produces paralytic shellfish toxins that affect marine fisheries and aquaculture as well as ecosystem and human health worldwide. This harmful algal species is extremely sensitive to environmental conditions and potentially to future climate change. Using a generalised additive mixed model (GAMM) we studied the potential effects of changing salinity and temperatures on A. catenella bloom (≥ 1000 cells L-1) occurrence along Canada’s East Coast throughout the 21st century. Our GAMM was applied to two high greenhouse gas emissions scenarios (RCP 8.5) and one mitigation scenario (RCP 4.5). Under present-day conditions, our model successfully predicted A. catenella’s spatio-temporal distribution in Eastern Canada. Under future conditions, all scenarios predict increases in bloom frequency and spatial extent as well as changes in bloom seasonality. Under one RCP 8.5 scenario, A. catenella bloom occurrences increased at up to 3.5 days per decade throughout the 21st century, with amplified year-to-year variability. Blooms expanded into the Gulf of St. Lawrence and onto the Scotian Shelf. These conditions could trigger unprecedented bloom events in the future throughout our study region. In all climate scenarios, the bloom season intensified earlier (May-June) and ended later (October). In some areas of the Gulf of St. Lawrence, the thermal habitat of A. catenella was exceeded, thereby locally reducing bloom risk during the summer months. We conclude that an increase in A. catenella’s environmental bloom window could further threaten marine fauna including endangered species as well as fisheries and aquaculture industries on Canada’s East Coast. Similar impacts could be felt in other coastal regions of the globe where warming and freshening of waters are intensifying.